Self-advocacy for first-year students in interior architecture design studios - Rauf, Hozan Latif; Gunce, Kagan; Ozersay, Munevver Ozgur (Open house international, 2020)
Purpose>The study aims to identify the issues that restrict students to show their real performance in the design due to lacking of self-advocacy skills and suggesting a new concept to overcome these difficulties.Design/methodology/approach>The current literature was surveyed to form a comprehensive understanding of the issue. A case study has been taken for three years and two groups of students were taken. Results achieved and discussed.Findings>The result of the study showed that those students who undergo an environment equipped with knowledge about self-advocacy can perform better and the success level is relatively higher amongst these students.Originality/value>This study contributes to the current literature an original knowledge that has not been previously written about (empowering self-advocacy amongst students of interior architecture). The profession of interior architecture is a relatively new profession and faces challenges in fixing its feet on the ground that is why the subject can add a real value to it to alleviate the challenge.